The Influence Of Transformational Leadership On Teacher Performance Through The Motivation Of Elementary School Teachers In Alok District, Sikka Regency, East Nusa Tenggara - Afloubun, Hubertina; Kuncono, Setio; Nafisah, A'isy Fiklil; Sumunu, Trenggono; Handayani, Sari (International Humanity Advance, Business & Sciences, 2025)
This study aims to analyze the influence of transformational leadership on work motivation and teacher performance, as well as examine the role of motivation as a mediating variable in elementary school teachers in Alok District, Sikka Regency, East Nusa Tenggara. The background of this research departs from the importance of the role of the principal as a leader who is able to create a positive work climate, raise enthusiasm, and inspire teachers to work with high motivation so that their performance increases. The research population includes all elementary school teachers in Alok District as many as 225 people, with a sample of 144 respondents selected using purposive sampling techniques based on the criteria of a minimum working period of three years. Data was collected through questionnaire deployment and analyzed using the Partial Least Square (PLS) approach with the help of SmartPLS 4.0 software. The results of the study show that transformational leadership has a positive and significant effect on teachers' work motivation. In addition, work motivation has been proven to have a positive and significant effect on teacher performance. Other findings show that work motivation plays a role as a mediating variable between transformational leadership and teacher performance. This confirms that school principals with a transformational leadership style can increase work motivation which has a direct impact on improving teacher performance in elementary schools.